Bleak house - Geraghty, Christine (London : Palgrave Macmillan, 2012)
This analysis of the BBC's 'Bleak House' explores this critically acclaimed production in terms of its adaptation status, narrative organisation, acting, setting and mise-en-scene, while also using it to comment on more general issues in television studies.
Includes bibliographical references ( p. 128-131) and index.
Keywords: Bleak House (Television program : 1985)